Effects of different intensities of repetitive peripheral magnetic stimulation on corticospinal excitability and motor performance in healthy humans - Ayu Omiya; Kanau Shitara; Dai Miyazaki; Mitsuhiro Nito (PLoS ONE, 2026)
Repetitive peripheral magnetic stimulation (rPMS) has been applied in clinical settings to enhance the recovery of motor function following central nervous system lesions. However, the optimal intensity of rPMS for inducing neural plasticity and the mechanisms behind its action are not understood. We investigated the impacts of rPMS at two different stimulus intensities on motor performance and the motor-evoked potentials (MEPs) elicited by transcranial magnetic stimulation in the arm muscles of 20 healthy adults. The biceps brachii (BB) muscle was subjected to rPMS in a 2-s ON and 2-s OFF cycle (for a total duration of 15 min). Two levels of rPMS were used: one that was sufficient to cause muscle contraction and one that was not. When investigating the effects on motor performance, an increase in elbow flexion torque and muscle activity was observed after rPMS at an intensity that elicited muscle contraction, whereas no significant changes were observed after rPMS at an intensity that did not cause muscle contraction. The MEPs of the BB increased after rPMS at an intensity that elicited muscle contraction, but no significant changes were observed after rPMS at an intensity that did not cause muscle contraction. Cervicomedullary MEP elicited by transmastoid electrical stimulation did not change after rPMS, implying that the increase in MEP was not accompanied by changes in the efficacy of cortico-motoneuronal synaptic transmission. These findings suggest that rPMS-induced muscle contraction can increase corticospinal excitability while maintaining spinal motoneuron excitability, thereby improving motor performance.